2021
DOI: 10.1177/20551029211012199
|View full text |Cite
|
Sign up to set email alerts
|

Maternal mental health and child well-being in Nigeria: A systematic review

Abstract: Maternal mental health distress has a disease burden of severe adverse effects for both mother and child. This review identified maternal mental health concerns, their impact on child growth and the current practice of maternal healthcare for both mothers and their children in Nigeria. The Population, phenomenon of Interest and Context (PICo) model was adopted to formulate the review strategy, and five databases were searched for published articles between 1999 and 2019. Databases include Scopus, PubMed, ProQu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…1,4 Poverty is linked to psychological symptoms through avenues including economic stressors, impaired parenting and exposure to community violence, lack of healthcare resources and facilities. [5][6][7] However, some studies have identified protective strategies that may buffer the impact of poverty on child development. These coping strategies include mobilising the family, seeking social support 5 and positive parenting.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…1,4 Poverty is linked to psychological symptoms through avenues including economic stressors, impaired parenting and exposure to community violence, lack of healthcare resources and facilities. [5][6][7] However, some studies have identified protective strategies that may buffer the impact of poverty on child development. These coping strategies include mobilising the family, seeking social support 5 and positive parenting.…”
Section: Introductionmentioning
confidence: 99%
“…3,8 However, there are significant gaps in knowledge regarding the efficacy of parenting programmes for improving child outcomes in LMICs. 7,10 Parenting and psychological interventions can be delivered during home visits, clinic visits or communitybased sessions. 12 These can be made effective by adapting the curriculum that is culturally relevant for LMICs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Discrimination against mental illness in Africa has often been documented in published literature (Jidong et al, 2021a). Such discriminatory acts among the general population sometimes arise from misinformation about mental disorders (Jidong et al, 2021b). In Nigeria, some studies have explored lived experiences of maternal anxiety and depression (e.g., Jidong et al, 2021c); however, there is a dearth of literature investigating how the general public views individuals with BDs.…”
Section: Introductionmentioning
confidence: 99%